Neurodegeneration-Associated Proteins in Human Olfactory Neurons Collected by Nasal Brushing - Brozzetti, Lorenzo; Sacchetto, Luca; Cecchini, Maria Paola; Avesani, Anna; Perra, Daniela; Bongianni, Matilde; Portioli, Corinne; Scupoli, Maria; Ghetti, Bernardino; Monaco, Salvatore; Buffelli, Mario; Zanusso, Gianluigi (Frontiers in Neuroscience, 2020)
The olfactory neuroepithelium is located in the upper vault of the nasal cavity, lying on the olfactory cleft and projecting into the dorsal portion of the superior and middle turbinates beyond the mid-portion of the nasal septum. It is composed of a variety of cell types including olfactory sensory neurons, supporting glial-like cells, microvillar cells, and basal stem cells. The cells of the neuroepithelium are often intermingled with respiratory and metaplastic epithelial cells. Olfactory neurons undergo a constant self-renewal in the timespan of 2–3 months; they are directly exposed to the external environment, and thus they are vulnerable to physical and chemical injuries. The latter might induce metabolic perturbations and ultimately be the cause of cell death. However, the lifespan of olfactory neurons is biologically programmed, and for this reason, these cells have an accelerated metabolic cycle leading to an irreversible apoptosis. These characteristics make these cells suitable for research related to nerve cell degeneration and aging. Recent studies have shown that a non-invasive and painless olfactory brushing procedure allows an efficient sampling from the olfactory neuroepithelium. This approach allows to detect the pathologic prion protein in patients with sporadic Creutzfeldt–Jakob disease, using the real-time quaking-induced conversion assay. Investigating the expression of all the proteins associated to neurodegeneration in the cells of the olfactory mucosa is a novel approach toward understanding the pathogenesis of human neurodegenerative diseases. Our aim was to investigate the expression of α-synuclein, β-amyloid, tau, and TDP-43 in the olfactory neurons of normal subjects. We showed that these proteins that are involved in neurodegenerative diseases are expressed in olfactory neurons. These findings raise the question on whether a relationship exists between the mechanisms of protein aggregation that occur in the olfactory bulb during the early stage of the neurodegenerative process and the protein misfolding occurring in the olfactory neuroepithelium.